The use of Otto Diy as a pedagogical tool in schools: integrating programming and various subjects - Santana, Kayky Bittencourt; Silva, América Alves de Almeida; Souza, Rafaela Rodrigues Santos; Pereira, Luan Diego de Lima (Brazilian Journal of Production Engineering, 2024)
The constant advancement of technology has generated a growing demand for programming skills, highlighting the importance of technological education in the current pedagogical context. This article addresses this theme, offering an analysis of the integration of educational robotics in education. Otto DIY is highlighted as a viable solution for integrating robotics into the educational environment. The research was based on specialized sources, citations from renowned professionals, and analyses of websites focused on robotics and programming. The results support the importance and effectiveness of the proposed approach. It is concluded that educational robotics represents a unique and innovative opportunity in the contemporary educational landscape, reinforcing the need for its adoption to prepare students for the challenges of the technological future.